(untitled) (Journal of Comparative & International Higher Education, 2023)
As the U.S. continues to prioritize the internationalization of higher education, study-abroad participation has doubled in the last decades. To correspond with this increased interest and prepare students for an intercultural workforce, study abroad programs have diversified travel destinations to include countries on the continent of Africa, most of which have colonial histories. However, many scholars have contended with the problematic nature of study abroad programs, especially interactions with host countries in the Global South. Specifically, the depiction of Africa is often othering or in a subjugated manner. Additionally, there is a lack of concise scholarship on the representation of people and places of travel destinations in study abroad programs images. As such, this exploratory study uses a postcolonial lens to understand how Africa is represented in the imagery of study abroad programs at selected Research 1 universities in the U.S. Results of the study and practical implications are presented.